The Effect Of Leverage, Rupiah Exchange Rate, Panic Buying And Government-Borne Vat Incentives On Stock Price Before The Covid-19 Pandemic And During The Covid-19 Pandemic In Companies Registered On The Idx - Willy Hendarto; Margaretha Prihatiningsih (Journal of Law and Social Politics, 2023)
This study aims to analyze the effect of Leverage, Rupiah Exchange Rate, Panic buying and VAT incentives borne by the government on stock prices in properties & real estate sector companies listed on the Indonesia Stock Exchange. The period of this study was carried out for 4 years starting from 2018 to 2021. This study used secondary data in the form of annual reports and financial statements. The technique used in sampling is purposive sampling. This study shows that leverage has a calculated value of -3.495 and a signific value of 0.001 which means that leverage has a significant negative effect on stock prices. The rupiah exchange rate has a calculated value of 0.855 and a signific value of 0.396 this can be interpreted to mean that the rupiah exchange rate has a positive and insignificant influence on the stock price. Panic buying has a calculated value of 4,158 with a significance of 0.000, which can be interpreted to mean that panic buying has a significant positive effect on stock prices. The vat incentive borne by the government has a calculated value of 3.826 and a signific value of 0.000 which means that the vat incentive borne by the government has a significant positive effect on the stock price in the pre-covid-19 period. Research during the Covid-19 period showed that leverage had a calculated value of -0.804 and a signific value of 0.424, which means that leverage has no effect on stock prices. The rupiah exchange rate has a calculated value of -0.002 and a signific value of 0.998, this can be interpreted to mean that the rupiah exchange rate does not have an effect on the stock price. Panic buying has a calculated value of 7,426 with a significance of 0.000, which can be interpreted to mean that panic buying has a significant positive effect on stock prices. The vat incentive borne by the government has a calculated value of 7,261 and a signific value of 0.000 which means that the vat incentive borne by the government has a significant positive effect on the stock price.